Catalyst‐Free One‐Pot Plasma Chemical Conversion of Carbon Dioxide to Performic Acid by Water‐Sealed Dielectric Barrier Discharge. Issue 12 (13th June 2016) - Kawasaki, Mitsuo; Nakamura, Toshihiro; Morita, Tatsuo; Tachibana, Kunihide
Abstract : Artificial carbon fixation to organic materials is an important challenge to address the global warming issue. However, the currently prevalent strategies rely upon catalysts to overcome the high kinetic barrier in CO2 chemistry. We show that water‐sealed dielectric barrier discharge in atmospheric CO2 affords a facile and selective carbon fixation pathway to performic acid. To verify the unique mechanism of catalyst‐free one‐pot ideal sequence for carbon fixation, we present in‐depth analysis of how the process is controlled by various discharge parameters. We validate the vibrational excitation of CO2 as the major driving force for the reaction and illuminate the central role of the plasma/liquid‐water interface. Abstract : CO2 under atmospheric pressure is readily converted to performic acid by water‐sealed dielectric barrier discharge. A honneycombed electrode with a number of throughholes sustains the plasma–liquid water interface, playing crucial roles in the plasma chemical carbon fixation without catalysts to the commercially useful organic peracid. The vibrational excitation of CO2 provides the major driving force.